The Expression Level of BRCA2 and Its Changes during Chemotherapy in Patients with Different Pathological Types of Mammary Cancer - Yu HUANG; Min LUO; Junqing HUANG; Shaoxin HUANG; Liuxia WEI; Yumei ZHANG; Zhiming ZHANG (Tehran University of Medical Sciences, 2019)
Background: We aimed to investigate the expression level of breast cancer susceptibility gene 2 (BRCA2) and its changes during chemotherapy in patients with different pathological types of mammary cancer (MC). Methods: Overall, 102 patients treated in Affiliated Tumor Hospital of Guangxi Medical University, China from April 2013 to August 2017 were enrolled as experimental group, including 58 patients with noninvasive MC (group A) and 44 with invasive MC (group B). Fifty healthy volunteers at the same time were enrolled as control group. The relative expression of BRCA2 in the blood of MC patients was detected by real-time fluorescence quantitative PCR (FQ-PCR). Results: In the experimental group, the expression level of BRCA2 in group A was higher than that in group B before chemotherapy (P<0.001); the expression level in group A and group B 1 month after chemotherapy was higher than that before chemotherapy (P<0.001); the expression level in the both groups 3 months after chemotherapy was higher than that 1 month after chemotherapy (P<0.001); the expression level of BRCA2 in blood of group A increased gradually before, 1 month and 3 months after chemotherapy (P<0.001). The expression level of BRCA2 in blood of group B increased gradually at the same time points (P<0.001). Conclusion: BRCA2 is over-expressed in noninvasive MC patient and under-expressed in invasive MC patient. And it can be used as an index for monitoring the condition of MC patients with different pathological types during chemotherapy.